EFFECTS OF BACTERIAL LIGANDS OF PATTERN-RECOGNIZING RECEPTORS (PRR) ON MONOCYTE-LIKE THP-1 CELLS UPON THEIR TRANSENDOTHELIAL MIGRATION - E. P. Starikova; D. I. Sokolov; L. A. Burova; S. A. Sel’kov; I. S. Freidlin (Медицинская иммунология, 2014)
Abstract. The aim of study was to compare the influence of lipopolysaccharide (LPS) component from Gram-negative bacteria (E. coli 055:B5), and a lysate of Gram-positive bacterium (Streptococcus pyogenes, type M1, strain 40/58) upon transendothelial migration rates of monocyte-like cells (THP-1 strain). Both LPS and lysate of Streptococcus pyogenes acted as chemoattractants for THP-1 cells. he studied components of Streptococcus pyogenes proved to be more active stimulants of transendothelial THP-1 cell migration, than LPS from E. coli. During spontaneous transmigration of THP-1 cells through a monolayer of endothelial cells, augmented levels of chemokines (RANTES, MCP-1, IL-8, IP-10) were noticed, that were more pronounced in presence of LPS. Upon spontaneous transmigration of THP-1 cells through endothelial monolayer, the levels of proinflammatory cytokines (TNFα, IL-1β and IL-6) in cultural medium were found to be rather low. The transmigration-associated secretion of these cytokines increased in presence of LPS and Streptococcus pyogenes lysate. Incubation with these bacterial constituents did increase cytokine levels both in monoculture of THP-1 cells and in transmigration model. Our results suggest that the levels of THP-1 transendothelial migration depend mainly on activation of monocyte-like cells influenced by PRR-ligands from Streptococcus pyogenes lysate. (Med. Immunol., vol. 10, N 6, pp 571-576).